2013
DOI: 10.1074/jbc.m113.500926
|View full text |Cite
|
Sign up to set email alerts
|

Intramolecular Dynamics within the N-Cap-SH3-SH2 Regulatory Unit of the c-Abl Tyrosine Kinase Reveal Targeting to the Cellular Membrane

Abstract: Background: c-Abl regulates cell signaling and participates in leukemia pathogenesis via Bcr-Abl chimeric protein.Results: N-Cap and SH3 residues acquire μs-ms motions within the regulatory unit and membrane anchoring upon protein activation.Conclusion: N-Cap-myristoyl tether triggers c-Abl to anchor membrane because of μs-ms dynamics within this regulatory region.Significance: Binding to the membrane is lost in Bcr-Abl chimeric protein, which underlies leukemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 38 publications
0
20
0
Order By: Relevance
“…1a): an unstructured N-terminal region referred to as the cap (residues 1–80), the SH3 domain (residues 85–138), a short linker referred to as the connector SH3/2 (residues 139–152) that connects the SH3 to the SH2 domain (residues 153–237), and a linker (linker SH2-KD ; residues 238–250) that connects the SH2 to KD (residues 255–534) 8 . To delineate the conformational landscape of Abl RM, we used NMR 27,28 to determine the intrinsic structural and dynamic properties of the isolated Abl RM (residues 1–255) (Supplementary Fig. 1a,b).…”
Section: Resultsmentioning
confidence: 99%
“…1a): an unstructured N-terminal region referred to as the cap (residues 1–80), the SH3 domain (residues 85–138), a short linker referred to as the connector SH3/2 (residues 139–152) that connects the SH3 to the SH2 domain (residues 153–237), and a linker (linker SH2-KD ; residues 238–250) that connects the SH2 to KD (residues 255–534) 8 . To delineate the conformational landscape of Abl RM, we used NMR 27,28 to determine the intrinsic structural and dynamic properties of the isolated Abl RM (residues 1–255) (Supplementary Fig. 1a,b).…”
Section: Resultsmentioning
confidence: 99%
“…One possibility is that PxxPxR motifs could facilitate structural stability in the SH3 domain-containing proteins. In support of this idea, recent studies have shown that the linker regions surrounding SH3 and other interaction domains in Abl and PLC-γ1 regulate the dynamics of the interaction cassettes [3941]. The PxxPxR motifs could be critical for the stable binding with SH3 domains.…”
Section: Discussionmentioning
confidence: 99%
“…Src family member abl also binds membranes through its SH4 and SH3 domains, and abl translocation changes the downstream events induced by the kinase (de Oliveira et al, 2013). The bcr-abl hybrid associated with leukemia shows lower membrane association than the nononcogenic form and alteration of tyrosine kinase-membrane binding may be a future line of cancer therapy.…”
Section: Activation Of Src By Pa Pi4p Uroplakin Pld G Proteins Cmentioning
confidence: 99%